Formulation and invitro Characterisation of Mucoadhesive Microspheres of Oseltamivir by Ionic Gelation Method - S.Allimalarkodi; C.Lokesh; V.Ganesan (International Journal of Pharmacy and Analytical Research, 2014)
The objective of the present study was to prepare and evaluate the mucoadhesive microspheres of oseltamivir. Oseltamivir microspheres were prepared by ionotropic gelation method using polymers such as HPMC (K 100 M), carbopol 940P, sodium CMC, sodium alginate. Totally 10 different formulations of oseltamivir were prepared by using the above polymers. The microspheres were characterised for drug content, entrapment efficiency, swelling index, mucoadhesive property by in vitro wash-off test and in-vitro drug release. The formulation F8 was selected as an ideal formulation based on the in vitro release profile which showed a controlled drug release of 86.11% up to 12 hours in acidic buffer of pH 1.2. Surface morphology (SEM analysis) and drug-polymer interaction studies (FT-IR analysis) were performed only for all the formulations. The microspheres were smooth and elegant in appearance showed no visible cracks as confirmed by SEM and FTIR studies indicated the lack of drug-polymer interactions in the ideal formulation F8. The in vitro release data of all microsphere formulations were plotted in various kinetic equations to understand the mechanisms and kinetics of drug release. The ideal formulation, F8 followed Higuchi model kinetics.